Intervention Through Sport: Positive Youth Development with Autism Spectrum Disorders and Practicing Thai Boxing. Research in the Parent-Child Dyad - Mateusz Barłóg; Rafał Tomasik (Facta Simonidis, 2024)
The article discusses the positive development of youth diagnosed with autism spectrum disorders through sports. The concept of positive development focuses on strengthening the natural potential of teenagers and preparing them for the challenges of adulthood. The article presents a report from a quantitative study conducted in a group of 72 people, including 36 teenagers diagnosed with autism spectrum disorders and 36 of their parents. The relationship between positive development of youth and life satisfaction and the level of interpersonal competences of teenagers was analyzed. The results indicate that positive development of youth diagnosed with autism spectrum disorders correlates with life satisfaction and selected interpersonal competences. The discussion of the results presents practical recommendations for strengthening the potential of teenagers with autism spectrum disorders.